2019
DOI: 10.1177/0272684x19874974
|View full text |Cite
|
Sign up to set email alerts
|

Teaching a Health Equity Course at a Midwestern Private University—A Pilot Study

Abstract: Teaching about health disparities and health equity at a 4-year institution is imperative. Unfortunately, there is a lack of empirical research demonstrating this concept and the proper way to develop a course. As a result, this research attempted to assess the effectiveness of developing and teaching this course centered on the social determinants of health (SDH). Using a 30-question Attribution of Health Disparities Assessment, data were collected on students’ attitudes and beliefs about the relevancy of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…This finding is consistent with findings from a national public opinion survey of non-Indigenous Canadians that demonstrated that men were twice as likely to blame Indigenous Peoples themselves for the inequality they face compared to woman [ 3 ]. Similarly, gender differences or political views did not differ based on individual or structural attributions [ 10 , 57 ], this aligns with the findings of our study. Our study also suggest that women were more likely to express greater support for government social action and policies following the intervention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with findings from a national public opinion survey of non-Indigenous Canadians that demonstrated that men were twice as likely to blame Indigenous Peoples themselves for the inequality they face compared to woman [ 3 ]. Similarly, gender differences or political views did not differ based on individual or structural attributions [ 10 , 57 ], this aligns with the findings of our study. Our study also suggest that women were more likely to express greater support for government social action and policies following the intervention.…”
Section: Discussionsupporting
confidence: 91%
“…The good news is that educational interventions that teach about the social and structural determinants of group-based inequities in other contexts have been shown to increase external causal attributions [ 10 ] and reduce negative intergroup attitudes [ 11 ]. In line with this research, the TRC of Canada issued a call in its 2015 final report for the implementation of antiracist educational interventions and cultural competency training for healthcare professionals.…”
mentioning
confidence: 99%
“…There are several reports of social justice-based theoretical frameworks that serve as underpinnings for course development (Faloughi and Herman, 2021;Crawford et al, 2022), but limited published literature exists on individual assignments within public health coursework that engage students with concepts of health equity and social justice. Other health-related fields elucidate how including content on health equity (Braun et al, 2020;Denizard-Thompson et al, 2021;Bunting and Benjamins, 2022;Recto et al, 2022) and social justice (Hellman et al, 2018;Hughes et al, 2022;Shahzad et al, 2022) has not only improved students' understanding of the social determinants of health but also contributed to providing impartial care for vulnerable and/or marginalized populations. Consequently, through intentionally integrating culturally responsive and culturally relevant pedagogies within public health education, we can train the future public health workforce to engage with and practice social empathy and holistic community advocacy.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to advance HE have focused on training and development to increase the knowledge, attitudes, and beliefs (KABs) of physicians and other providers 3. Studies find that training and education on HE concepts increase provider KABs, including knowledge of health care disparities,4 knowledge about racial and ethnic disparities and ways to eliminate them,5 and attitudes and beliefs about health disparities and their relevancy to health behavior and outcomes 6. However, many health-related organizations and institutions that do not provide direct clinical services also can benefit from training on HE and have an impact on health disparities and health outcomes.…”
mentioning
confidence: 99%
“…3 Studies find that training and education on HE concepts increase provider KABs, including knowledge of health care disparities, 4 knowledge about racial and ethnic disparities and ways to eliminate them, 5 and attitudes and beliefs about health disparities and their relevancy to health behavior and outcomes. 6 However, many health-related organizations and institutions that do not provide direct clinical services also can benefit from training on HE and have an impact on health disparities and health outcomes. According to RWJF, advancing HE requires building a culture of health by making health a shared value, fostering cross-sector collaboration, creating healthier and more equitable communities, and strengthening the integration of health services and systems.…”
mentioning
confidence: 99%